TNFα: TNFR1 signaling inhibits maturation and maintains the pro-inflammatory programming of monocyte-derived macrophages in murine chronic granulomatous disease - Gibbings, Sophie L.; Haist, Kelsey C.; Redente, Elizabeth F.; Henson, Peter M.; Bratton, Donna L. (Frontiers in Immunology, 2024)
Loss of NADPH oxidase activity results in proinflammatory macrophages that contribute to hyperinflammation in Chronic Granulomatous Disease (CGD). Previously, it was shown in a zymosan-induced peritonitis model that gp91 phox-/-(CGD) monocyte-derived macrophages (MoMacs) fail to phenotypically mature into pro-resolving MoMacs characteristic of wild type (WT) but retain the ability to do so when placed in the WT milieu. Accordingly, it was hypothesized that soluble factor(s) in the CGD milieu thwart appropriate programming. We sought to identify key constituents using ex vivo culture of peritoneal inflammatory leukocytes and their conditioned media. First, more extensive phenotyping by flow cytometry defined normal MoMac maturation and demonstrated failure of maturation of CGD MoMacs both ex vivo and in vivo. Protein components, and specifically TNFa, produced and released by CGD neutrophils and MoMacs into conditioned media was identified as critical to preventing maturation. Exogenous addition of TNFa inhibited WT MoMac maturation, and its neutralization allowed maturation of cultured CGD MoMacs. TNFa neutralization also reduced production of IL-1b, IL-6 and CXCL1 by CGD cells though these cytokines played no role in MoMac programming. Finally, TNFa signaling via TNFR1 was established as MoMacs lacking TNFR1 matured more normally in the CGD milieu both ex vivo and following adoptive transfer in vivo. These data lend mechanistic insights into the utility of TNFa blockade in CGD and to other diseases where such therapy has been shown to be beneficial.